Analysis of Latency, Blocking Probability and Network Utilization for a Specific Routing and Spectrum Assignment Algorithm, in Elastic Optical Networks - Kocevska, Teodora; Latkoski, Pero; Porjazoski, Marko; Popovski, Borislav (Acta Polytechnica Hungarica, 2020)
The emergence of new ICT applications has triggered significant growth in data traffic volumes. As a result, novel flexible and adaptive concepts for optical network management has emerged, in order to meet the heterogeneous and variable traffic demands. Efficient spectrum usage has become one of the most important issues, since the optical spectrum is not an infinite resource. Today’s WDM (Wavelength Division Multiplexing) technology is inappropriate, due to the fixed spectrum grid it uses. The elastic optical networks (EON) will overcome these problems. Finding an efficient RSA (Routing and Spectrum Allocation) algorithm is very important for resourceful use of the network. This paper extends the current research knowledge regarding the intelligent RSA algorithm with support for different Class of Service (CoS). It assumes a coexistence of two traffic categories in the network, along with а central Software Defined Networking (SDN) controller. Furthermore, a dynamic RSA algorithm is used with two controlling coefficients to determine the priority of different classes. The performance of the algorithm and the impact of the controlling coefficients on several performance metrics (e.g. average latency for data traffic, blocking probability, network utilization and network efficiency) has been examined through MATLAB simulations. The obtained results indicate some complex influence of the data traffic load and spectrum-controlling RSA coefficient over the performance metrics. The results can help network operators not only define different CoS in their network, but to also finely tune its utilization, blocking probability and data traffic latency, which is crucial for the emerging 5G communication networks.
Keywords: Elastic Optical Networks; Software Defined Networking; RSA; 5G; MATLAB